LABUBADAK (PELATIHAN PEMBUATAN BRIKET ARANG DARI KULIT SALAK) SEBAGAI ENERGI ALTERNATIF DAN BERNILAI EKONOMIS DI DESA SEKURA - Getisari, Melina; Doni, Dede Dona; Khairunisa, Sri (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Sekura is one of many regions in West Kalimantan that almost of the local society work as a farmer. Palm fruit is one of the amounts farming commodity. The advantages of palm fruit that do not known yet by local society in Sekura, keep many specialty hidden in the palm fruitâs skin. Palm fruitâs skins can use as briket charcoal. Briket charcoal is one variant of charcoals that have been processed as a practical product and economist, and use to alternative energy. Basic training of processing making briket charcoal from skin of palm fruit have been have a permission steps, also the materials and tools. By this training or socialization process the society have been get new knowledge about advantages of regionâs potential, and how to reduce the rubbish heap. So, in the future they can improve the prosperous and the economic society.